2020
DOI: 10.1016/j.omtn.2020.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Transcriptome Sequencing Identifies Key Differentially Expressed mRNAs, miRNAs, lncRNAs, and circRNAs Associated with CHOL

Abstract: To systematically evaluate the whole-transcriptome sequencing data of cholangiocarcinoma (CHOL) to gain more insights into the transcriptomic landscape and molecular mechanism of this cancer, we performed whole-transcriptome sequencing based on the tumorous (C) and their corresponding non-tumorous adjacent to the tumors (CP) from eight CHOL patients. Subsequently, differential expression analysis was performed on the C and CP groups, followed by functional interaction prediction analysis to investigate gene-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…RNA sequencing technology was provided by Novogene (Beijing, China). Differentially expressed circRNAs, miRNAs, and mRNAs were analyzed as previous reported [ 15 ] (Additional file 1 : Table S7–9).…”
Section: Methodsmentioning
confidence: 99%
“…RNA sequencing technology was provided by Novogene (Beijing, China). Differentially expressed circRNAs, miRNAs, and mRNAs were analyzed as previous reported [ 15 ] (Additional file 1 : Table S7–9).…”
Section: Methodsmentioning
confidence: 99%
“… 17 , 21 , 22 Moreover, whole-transcriptome sequencing has revealed that there are 110 differentially expressed circRNAs in CCA tissues in contrast to adjacent normal tissues. 23 Previous study uncovered that circRNA circ_0000284 aroused the malignant phenotype of CCA cells. 21 Also, circRNA circCDR1as exerted a promoting impact on the malignancy of CCA cells through sponging miR-641.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have utilized circRNA-containing whole-transcriptome sequencing technology, which allows accurate examination of the transcriptomic landscape of CCA. Chu et al [105] explored the molecular mechanisms of CCA by performing circRNA-containing whole-transcriptome sequencing and validation with the TCGA database. In this study, miR-144-3p was identified to be located in the center of the ceRNA network and might play an important role in the pathogenesis of CCA.…”
Section: Cerna Regulatory Networkmentioning
confidence: 99%